Re-Conceptualisation of Agriculture Information System for Uganda - Oyo, Benedict; Kaye, Milton; Nkalubo, Lenard (TSEST Transaction on Electrical and Electronic Circuits and Systems, 2014)
Researchers and practitioners have over and again advocated for more funding to stimulate growth in the agricultural sector, but none provide more than anecdotal coverage of how increased funding translates into better livelohoods for the smallholder farmers. Based on experience with the earlier version of agriculture information system for Uganda, this paper identifies two performance gaps, namely, productivity and profitability gaps, and knowledge and skills gaps, as key to individual and hollistic empowerment of smallholder farmers. Mitigation measures for these gaps are explored through iterative agriculture information system architecture. The paper concludes that the impact of agriculture information system rests on its technical efficiency as informed by the architecture and its operational effectiveness arising from situational adoption strategies.
Keywords: Agricultural extension; Cooperatives; Smallholder farmers; Grassroots; Information technology